Meningkatkan Motivasi Belajar Siswa Kelas 3 pada Mata Pelajaran PPKN Di SDN 6 Ampenan melalu Penggunaan Media Wordwall Tahun Ajaran 2023/2024 - Sahrul, Sarul Hadi Gunawan; Suryani, Nur Rahmah; Musdat, Syaiful (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to examine the improvement of learning motivation among third-grade students in Civics (PPKN) at SDN 6 Ampenan through the use of Wordwall media during the 2023/2024 academic year. This research employed Classroom Action Research (CAR), with data collected through observation. The population consisted of 27 third-grade students at SDN 6 Ampenan. The results indicate a significant increase in student motivation, rising from 20% in the pre-action stage to 88% after the implementation of Wordwall media. These findings suggest that the use of Wordwall effectively enhances students’ motivation in learning PPKN.